The attitudes of English-as-a-Foreign-Language students towards the learning usefulness and benefits of Google-Drive for Collaborative Writing - Rosique-Martínez, Luis Alberto; Domínguez-Barrera, Gisela; Izquierdo, Jesús (Cinzontle, 2018)
This study examines undergraduate EFL learners’ perceptions of the usefulness of a web-based application for collaborative writing, namely Google Drive. Upon completion of a form-focused output-based language learning task using the Google Drive application for synchronous collaborative editing of documents, two students participated in an interview examining the computerized task’s accessibility, language learning benefits and its limitations. Students showed positive attitudes towards the use of technological tools in language education. Furthermore, they perceived language gains in regard to grammar, vocabulary, and punctuation. Some difficulties acknowledged by the students related to initial accessibility, distraction, and disorganization of turns for written contribution. In light of these findings, some pedagogical suggestions are put forward for the integration of computer-enhanced interactional tasks to promote L2 written output in the L2 classrom.